Lassen Volcanic Fumaroles and Hot Springs: Analog for Mars - McHenry, Lindsay J.; Gerard, Teri L.; Walters, Gabrielle L. (Proceedings of the Wisconsin Space Conference, 2014)
We are conducting a pilot study on the hydrothermal alteration of lavas at Lassen Volcanic National Park as an analog for potential hydrothermal deposits on Mars. Lassen has hot springs and fumaroles that have altered its lavas into silica, sulfates, and phyllosilicates, all mineral types also identified on Mars. Hydrothermal environments were likely common on Mars (due to evidence of early aqueous and a long record of volcanic activity), and such environments could have remained habitable long after the surface cooled and desiccated. However, some hydrothermal environments are more habitable than others, and being able to distinguish between the deposits of hostile acid-sulfate fumarole and more accommodating near-neutral hot spring environments can provide clues to habitability. Lassen hydrothermal environments produce silica by both acid-sulfate leaching and precipitation from neutral hydrothermal waters, both of which have been suggested as potential origins for deposits in Columbia Hills of Gusev Crater on Mars.Â